Mammalian oocytes are targets for prostaglandin E2 (PGE2) action - VandeVoort Catherine A; McGinnis Lynda K; Duffy Diane M; Christenson Lane K (BMC, 2010)
Abstract Background The ovulatory gonadotropin surge increases synthesis of prostaglandin E2 (PGE2) by the periovulatory follicle. PGE2 actions on granulosa cells are essential for successful ovulation. The aim of the present study is to determine if PGE2 also acts directly at the oocyte to regulate periovulatory events. Methods Oocytes were obtained from monkeys and mice after ovarian follicular stimulation and assessed for PGE2 receptor mRNA and proteins. Oocytes were cultured with vehicle or PGE2 and assessed for cAMP generation, resumption of meiosis, and in vitro fertilization. Results Germinal vesicle intact (GV) oocytes from both monkeys and mice expressed mRNA for the PGE2 receptors EP2, EP3, and EP4. EP2 and EP4 proteins were detected by confocal microscopy in oocytes of both species. Monkey and mouse oocytes responded to PGE2 as well as agonists selective for EP2 and EP4 receptors with elevated cAMP, consistent with previous identification of EP2 and EP4 as Gαs/adenylyl cyclase coupled receptors. Incubation of mouse GV stage oocytes with PGE2 delayed oocyte nuclear maturation in vitro, but PGE2 treatment did not alter the percentage of mouse oocytes that fertilized successfully. PGE2 treatment also decreased the percentage of monkey oocytes that resumed meiosis in vitro. In contrast with mouse oocytes, the percentage of monkey oocytes which fertilized in vitro was lower after treatment with PGE2. Monkey oocytes with intact cumulus showed delayed nuclear maturation, but fertilization rate was not affected by PGE2 treatment. Conclusions Monkey and mouse oocytes express functional PGE2 receptors. PGE2 acts directly at mammalian oocytes to delay nuclear maturation. Surrounding cumulus cells modulate the effect of PGE2 to alter subsequent fertilization.